Trade, Tragedy, and the Commons - Copeland, Brian R; Taylor, M. Scott (American Economic Review, 2009)
We develop a theory of resource management where the degree to which countries escape the tragedy of the commons is endogenously determined and explicitly linked to changes in world prices and other possible effects of market integration. We show how changes in world prices can move some countries from de facto open access situations to ones where management replicates that of an unconstrained social planner. Not all countries can follow this path of institutional reform and we identify key country characteristics (mortality rates, resource growth rates, technology) to divide the world's set of resource rich countries into Hardin, Ostrom and Clark economies. Hardin economies are not able to manage their renewable resources at any world price, have zero rents and suffer from the tragedy of the commons. Ostrom economies exhibit de facto open access and zero rents for low resource prices, but can maintain a limited form of resource management at higher prices. Clark economies can implement fully efficient management and do so when resource prices are sufficiently high. The model shows heterogeneity in the success of resource management is to be expected, and neutral technological progress works to undermine the efficacy of property rights institutions.